Design in motion : applying design principles to filmmaking - Hilton, Penny (London, England : Zed Books, 2020)
With an abundance of information on how to create motion graphics already available, 'Design in Motion' focuses on the why of moving image and less about the how. By unpacking the reasons behind screen designer's production choices, each chapter deconstructs examples of motion graphics by drawing on case studies of both familiar examples from contemporary cinema and unseen work from postgraduate motion graphic designers. It examines the value of image, text, motion, camera and transitions, explaining in detail why some methods work, while others fail. Whether you work in info-graphics, documentary or design, this book is structured to follow the production process and, together with its multimedia companion website, will be a by-your-side companion to guide you through your next project.
Foundations -- Audience -- Structure -- Sound -- Composition -- Camera -- Form -- Colour -- Text and Information -- Editing.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Cinematography -- Special effects; Computer graphics -- Design; Film production: technical & background skills; Electronic books